Diabetic retinopathy from a sociocultural perspective (Salud, Arte y Cuidado, 2025)
Diabetes mellitus has been considered one of the health scourges. The increase in its prevalence and the disabling nature of its complications show the need for projections that guarantee early diagnosis and adequate management. Diabetic Retinopathy is a neurovascular complication of Diabetes Mellitus, which produces blindness and mainly affects the working-active and elderly population. There is a social dependency of patients with Diabetic Retinopathy, as they have decreased vision, slow evolution and require a long period of treatment; the present study has the objective of problematizing, through a dialogic, the impact of Diabetic Retinopathy on the patient from the health and sociocultural aspects. Depending on the clinical stage of the disease, they may have a visual disability that can lead to blindness, which makes them people in need of help to carry out their daily activities, they need financial support because they are unable to perform their work and support themselves. Of his family, needing rehabilitation to be able to integrate into society.
Keywords: diabetes mellitus; diabetic retinopathy; sociocultural impact